2017
DOI: 10.2217/nmt-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcranial Direct Current Stimulation to Treat Symptoms in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Transcranial direct current stimulation (tDCS) has recently been investigated as a potential nonpharmacological treatment for individuals with mild cognitive impairment (MCI) and Alzheimer's disease (AD). A comprehensive literature search was performed on tDCS studies published until March 2017 using MEDLINE, Embase and PsychINFO databases. 12 articles with a total of 202 MCI or AD participants were included. Although ten of the 12 studies demonstrated positive findings with tDCS, two studies reported no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 79 publications
1
29
0
2
Order By: Relevance
“…35 In one review article, 10 out of 12 studies in patients with AD or MCI showed improved cognition with tDCS. 40 Studies in patients with cognitive disorders have shown the benefits of tDCS combined with cognitive tasks on visual memory, attention and executive function. 41,42 The positive effects of this combination could be due to tDCS acutely improving attention or executive function during the cognitive task leading to improved learning.…”
Section: Adverse Effects and Adherencementioning
confidence: 99%
“…35 In one review article, 10 out of 12 studies in patients with AD or MCI showed improved cognition with tDCS. 40 Studies in patients with cognitive disorders have shown the benefits of tDCS combined with cognitive tasks on visual memory, attention and executive function. 41,42 The positive effects of this combination could be due to tDCS acutely improving attention or executive function during the cognitive task leading to improved learning.…”
Section: Adverse Effects and Adherencementioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a noninvasive neuromodulation technique that delivers a constant low-intensity subthreshold direct current to specific regions of the brain through electrodes placed on the scalp, thereby regulating cell transmembrane potential depolarization and hyperpolarization (Bindman et al, 1962;Nitsche and Paulus, 2000) and altering neuronal activity and excitability of the cerebral cortex (Nitsche et al, 2008;Stagg et al, 2018). A number of clinical and basic studies have found that tDCS treatment can improve memory and cognitive dysfunction in patients and animal with AD (Yu et al, 2014;Hsu et al, 2015;Liu et al, 2017;Cruz Gonzalez et al, 2018). However, few studies have validated tDCS in the preclinical AD phase, and little is known about the mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Including several covariates to for inter-individual differences in tDCS response [108][109][110] strengthened the observed beneficial effect of training success in MCI (Model 1). Specifically, lower age, female gender, a lower BDI baseline score, and higher MWT score were associated with increased training success.…”
Section: Variability Of Atdcs Effectsmentioning
confidence: 85%